Impact of healthy living behavior, food handling sanitation on gastroenteritis incidence among female students at madrasah tsanawiyah in bogor city - Dwi Maharani, Clara; Widiyanti, Dian; Arsyad, Muhammad (Jurnal EduHealth, 2024)
Gastroenteritis is an inflammatory disease of the digestive tract with a high prevalence in Indonesia, which has detrimental effects on sufferers, especially children. Gastroenteritis is often associated with the consumption of unhygienic food and is not handled properly. Gastroenteritis cases occur quite often in students who live in boarding schools. This study aims to determine the relationship between sanitation, food management, and Clean and Healthy Living Behavior (PHBS) with the incidence of gastroenteritis among female students at a Tsanawiyah Madrasah in Bogor City. This research uses a cross-sectional research design with a qualitative analytical approach. Research respondents were taken from 95 female students selected through simple random sampling. Data were obtained through questionnaires regarding knowledge of gastroenteritis, PHBS, and observations of sanitation and food processing practices. The results showed that the majority of respondents (75.8%) had sufficient knowledge about gastroenteritis, while 60% of respondents indicated sufficient PHBS efforts. Based on the results of observations, food processing sanitation is included in the category of being quite good (60%). From this study it can be concluded that there is no significant relationship between knowledge, PHBS behavior, and sanitation in food processing on the incidence of gastroenteritis. In Islamic terms, knowledge not only shows faith and piety, but can also contribute to the prevention of gastroenteritis.